Complete genome sequence of Mesorhizobium opportunistum type strain WSM2075T. Issue 2 (September 2013) - Reeve, Wayne; Nandasena, Kemanthi; Yates, Ron; Tiwari, Ravi; O'Hara, Graham; Ninawi, Mohamed; Chertkov, Olga; Goodwin, Lynne; Bruce, David; Detter, Chris; Tapia, Roxanne; Han, Shunseng; et al.
Abstract Mesorhizobium opportunistum strain WSM2075T was isolated in Western Australia in 2000 from root nodules of the pasture legumeBiserrula pelecinus that had been inoculated withM. ciceri bv. biserrulae WSM1271. WSM2075T is an aerobic, motile, Gram negative, non-spore-forming rod that has gained the ability to nodulateB. pelecinus but is completely ineffective in N2 fixation with this host. This report reveals that the genome ofM. opportunistum strain WSM2075T contains a chromosome of size 6, 884, 444 bp, encoding 6, 685 protein-coding genes and 62 RNA-only encoding genes. The genome contains no plasmids, but does harbor a 455.7 kb genomic island fromMesorhizobium ciceri bv. biserrulae WSM1271 that has been integrated into a phenylalanine-tRNA gene.